2015
DOI: 10.1523/jneurosci.5207-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Axonal and Schwann Cell BACE1 Is Equally Required for Remyelination of Peripheral Nerves

Abstract: Inhibition of ␤-site APP cleaving enzyme 1 (BACE1) is being pursued as a therapeutic target for treating patients with Alzheimer's disease because BACE1 is the sole ␤-secretase for generating ␤-amyloid peptide. Knowledge regarding the other cellular functions of BACE1 is therefore critical for the safe use of BACE1 inhibitors in human patients. BACE1 deficiency in mice causes hypomyelination during development and impairs remyelination in injured sciatic nerves. Since BACE1 is expected to be ubiquitously expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 53 publications
1
39
0
1
Order By: Relevance
“…Although associated with β‐cleavage of APP, leading to greater Aβ and βCTF expression, attenuation of Bace1 levels by MCS may indicate a counterintuitive normalization of APP processing in vulnerable neurons that reflects the importance of steady‐state Aβ and βCTF levels, underscoring the importance of evaluating βCTF expression in DS/AD models (Jiang et al, ). Alternatively, Bace1 deficiency may be considered detrimental, as a loss of Bace1 expression impairs myelination (Hu, Hu, Dai, Trapp, & Yan, ) and causes hippocampal synaptic deficits (Petrus & Lee, ; Wang et al, ; Zhu et al, ), illustrating the need for normative Bace1 levels. MCS also restores the normal expression of two truncated forms of tau ( Mapt2N6D and Mapt2N6P ).…”
Section: Discussionmentioning
confidence: 99%
“…Although associated with β‐cleavage of APP, leading to greater Aβ and βCTF expression, attenuation of Bace1 levels by MCS may indicate a counterintuitive normalization of APP processing in vulnerable neurons that reflects the importance of steady‐state Aβ and βCTF levels, underscoring the importance of evaluating βCTF expression in DS/AD models (Jiang et al, ). Alternatively, Bace1 deficiency may be considered detrimental, as a loss of Bace1 expression impairs myelination (Hu, Hu, Dai, Trapp, & Yan, ) and causes hippocampal synaptic deficits (Petrus & Lee, ; Wang et al, ; Zhu et al, ), illustrating the need for normative Bace1 levels. MCS also restores the normal expression of two truncated forms of tau ( Mapt2N6D and Mapt2N6P ).…”
Section: Discussionmentioning
confidence: 99%
“…We show that in the case of either a BACE1‐null nerve segment transplanted into a WT recipient or a WT nerve segment transplanted into a BACE1‐null recipient, remyelination is equally impaired, as the increase in g‐ratio is almost identical (Hu et al . ). Nerve injury not only induces expression of BACE1, but also type I Nrg1 by Schwann cells.…”
Section: Functional Changes Via Bace1‐dependent Nrg1 Signalingmentioning
confidence: 97%
“…One mechanism by which peripheral neurons regulate levels of Nrg1 is through cleavage of the protein by β-site amyloid precursor protein cleaving enzyme 1 (BACE1), a process which seems to be positively regulated by the metallopeptidase Nardylisin [45]. Recently, it has been shown that BACE1 is also expressed in Schwann cells and that Schwann cell-derived BACE1 is as important as axonal BACE1 in controlling myelination [46,47]. …”
Section: Teamwork I: Neuronal Control Over Myelinationmentioning
confidence: 99%